Kinematical Analysis of Butterfly Stroke: Comparison of Three Velocity Variants - de Jesus, K.; de Jesus, K.; Figueiredo, P. A.; Gonçalves, P.; Vilas-Boas, J. P.; Fernandes, R. J. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Stroke mechanics are continuously emphasized on competitive swimming in order to minimize intracyclic velocity variation (IVV). However, nonetheless butterfly specific training series are conducted in different intensity zones, few is known about the behavior of biomechanical parameters, and their implications on IVV, at different training regimens. We aimed to compare the butterfly kinematical changes during 100m (between the 1st and 4th laps) at 3 swimming velocities and in-between these intensities. It was hypothesized that higher IVV is observed at the 4th lap of each 100m, and, when comparing the 100m performed at different intensities, lower IVV will occur at higher velocities. METHODS: Seven female swimmers performed a protocol of 3x100m butterfly at sub-maximal (60 and 80%, v60 and v80, respectively) and at maximal velocities (v100), with a 30min interval. Two above and below water cameras, positioned in the sagittal plane, were used for movement analysis. APASystem was used to calculate and analyze the velocity (v), stroke length (SL), stroke rate (SR) and IVV of the centre of mass. Kinematic analysis was conducted at the first (1st) and fourth (4th) lap of each 100m test. Significance was considered for p<0,05. RESULTS: Comparing swimming v between the 1st and 4th lap of each 100m, differences were only observed at v100 (with higher v values in the 1st 50 m split: 1.47±0.13 vs 1.23±0.08). When comparing the v60, v80 and v100, differences were found in the 1st lap between all the trials (1.47±0.13, 1.30±0.21 and 1.27±0.06, respectively for v100, v80 and v60). Considering SR, higher values were observed for the 1st lap comparing with the 4th lap in v60 (48.0±1.22 vs 46.8±3.03) and v100 (57.0±7.20 vs 52.8±2.40). When comparing swimming intensities, SR in the 1st and 4th step was always lower in v60 than in v100. SL tends to follow an inverse behaviour than SR, but without statistical significance. Regarding the IVV parameter, no differences were observed. However, a tendency for higher values at v60 comparing to v100 in the 1st lap (24.9±11.60 vs 16.40±8.50) and in the total 100m effort (17.5±5.00 vs 14.8±7.00) was perceived. DISCUSSION: The behavior of the v and stroking parameters observed followed the traditionally described when comparing different front crawl intensities. The non existence of differences regarding the IVV seems to evidence that the lower v and SR values observed in the v60 were not of sufficient magnitude to affect it.